Complex shaped ZnO nano- and microstructure based polymer composites: mechanically stable and environmentally friendly coatings for potential antifouling applications. Issue 10 (17th February 2016) - Hölken, Iris; Hoppe, Mathias; Mishra, Yogendra K.; Gorb, Stanislav N.; Adelung, Rainer; Baum, Martina J.
Abstract : For marine applications, the antifouling coatings have to fulfill various demands, like mechanical and UV-stability, being non-toxic and long lasting, etc . The presented investigations demonstrate the suitability of tetrapodal ZnO-polymer composite coatings for antifouling applications. Abstract : Since the prohibition of tributyltin (TBT)-based antifouling paints in 2008, the development of environmentally compatible and commercially realizable alternatives is a crucial issue. Cost effective fabrication of antifouling paints with desired physical and biocompatible features is simultaneously required and recent developments in the direction of inorganic nanomaterials could play a major role. In the present work, a solvent free polymer/particle-composite coating based on two component polythiourethane (PTU) and tetrapodal shaped ZnO (t-ZnO) nano- and microstructures has been synthesized and studied with respect to mechanical, chemical and biocompatibility properties. Furthermore, antifouling tests have been carried out in artificial seawater tanks. Four different PTU/t-ZnO composites with various t-ZnO filling fractions (0 wt%, 1 wt%, 5 wt%, 10 wt%) were prepared and the corresponding tensile, hardness, and pull-off test results revealed that the composite filled with 5 wt% t-ZnO exhibits the strongest mechanical properties. Surface free energy (SFE) studies using contact angle measurements showed that the SFE value decreases with an increase in t-ZnO filler amounts. The influence of t-ZnO on the polymerization reaction was confirmed by Fourier transform infrared-spectroscopy measurements and thermogravimetric analysis. The immersion tests demonstrated that fouling behavior of the PTU/t-ZnO composite with a 1 wt% t-ZnO filler has been decreased in comparison to pure PTU. The composite with a 5 wt% t-ZnO filler showed almost no biofouling.